Direct formation of transfer-free graphene as current spreading layers on n-ZnO nanorods/p-GaN light-emitting diodes. (13th June 2018) - Huang, Chun-Ying; Hsu, Fu-Fan; Wu, Chia-Ling; Chen, Ming-Liang; Tsai, Ping-Hung; Tong, Sian-Rong; Yeh, Ting-Wei; Lee, Ya-Ju
Abstract: Transfer-free graphene has been directly grown on ZnO nanorods (NRs)/p-GaN LEDs by a feasible approach involving rapid thermal annealing of amorphous carbon and nickel layers. Compared with conventional ZnO NRs/p-GaN LEDs without a current spreading layer, the current–voltage characteristic and electroluminescence performance are enhanced, mainly attributed to more efficient current spreading by the transfer-free graphene that conformally covers the entire surface of ZnO NRs, leading to better carrier injection. It is hence expected that our scheme will be of great importance for nanostructured LED arrays with large-scale fabrication.